2022
DOI: 10.1177/22799036221104161
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of psycho-educational counseling in pregnant women with preeclampsia: A systematic review

Abstract: Pre-eclampsia is one of the main causes of maternal mortality, premature birth and low birth weight in developing countries. In addition, this condition can lead to chronic diseases (including cardiovascular and renal diseases) in postpartum mothers. The purpose of this study was to review the effectiveness of psycho-educational counseling in pregnant women with preeclampsia. The methods of this study were using PRISMA guidelines, databases from Scopus, PubMed and ScienceDirect, were published 2016 until 2020,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Posiblemente, los profesionales en salud al reconocer que los THE se desencadenan a partir de la segunda mitad del embarazo, profundizan en las características de esta enfermedad (factores de riesgo, signos y síntomas, complicaciones) y promueven mayores conductas de autocuidado durante las consultas prenatales. Asimismo, el estudio realizado por Umamah et al (33), evidenció que el retraso en el inicio de la atención prenatal, genera que la educación y las recomendaciones de cuidado se impartan en forma tardía o incluso hasta el momento de la consulta de control posparto. Acorde con este mismo estudio, la consejería sobre los THE y sus comportamientos de autocuidado debería comenzar antes de la concepción y extenderse durante las visitas del control prenatal, con el propósito de fortalecer el empoderamiento, el conocimiento y la promoción de comportamientos en salud ante la prevención o control del riesgo de la hipertensión en el embarazo.…”
Section: Discussionunclassified
“…Posiblemente, los profesionales en salud al reconocer que los THE se desencadenan a partir de la segunda mitad del embarazo, profundizan en las características de esta enfermedad (factores de riesgo, signos y síntomas, complicaciones) y promueven mayores conductas de autocuidado durante las consultas prenatales. Asimismo, el estudio realizado por Umamah et al (33), evidenció que el retraso en el inicio de la atención prenatal, genera que la educación y las recomendaciones de cuidado se impartan en forma tardía o incluso hasta el momento de la consulta de control posparto. Acorde con este mismo estudio, la consejería sobre los THE y sus comportamientos de autocuidado debería comenzar antes de la concepción y extenderse durante las visitas del control prenatal, con el propósito de fortalecer el empoderamiento, el conocimiento y la promoción de comportamientos en salud ante la prevención o control del riesgo de la hipertensión en el embarazo.…”
Section: Discussionunclassified
“…Adequate knowledge of PE/E and its risk factors, symptoms, and complications, empowers patients and supports better healthcare decisions such as preventive measures and health seeking behaviour [18,49,50,51]. To understand participants' knowledge of PE/E, they were asked about their understanding and prior encounters.…”
Section: Knowledge Of Preeclampsia/eclampsia (Pe/e)mentioning
confidence: 99%
“…A good starting point is to develop targeted patient education on signs, symptoms, and risk factors, PE/E prevention strategies to reduce adverse complications [52]. Some of the delivery strategies could include lea ets, educational videos, one-on-one counselling sessions, and group education sessions [50,51].…”
Section: Attitude Towards Preventing Pe/ementioning
confidence: 99%
“…It is recommended that it should begin six weeks postpartum in patients these patients. The recommendations include risk modification strategies to decrease recurrence, i.e., strict monitoring of blood pressure, lifestyle improvement and modifications, and glycemic control should be attempted [ 46 ]. Crovetto et al reported that the Mediterranean diet and mindfulness help to reduce the incidence of small of age birth weight in newborns [ 47 ].…”
Section: Reviewmentioning
confidence: 99%
“…Hence, taking care of women with determinants of anxiety, as well as psychological counseling and timely referral to better and advanced diagnostic and treatment centers, can improve the quality of life and reduce maternal and fetal mortality and morbidity [ 43 ]. Women having low support from partners, family, and friends tend to have ineffective psychosocial resources, especially social stability and social participation, and thus receive insufficient emotional and psychological support from their social circle [ 46 ].…”
Section: Reviewmentioning
confidence: 99%